The Latitudinal Variability of Oceanic Rainfall Properties and Its Implication for Satellite Retrievals: 2. The Relationships Between Radar Observables and Drop Size Distribution Parameters. Issue 23 (14th December 2019) - Protat, Alain; Klepp, Christian; Louf, Valentin; Petersen, Walter A.; Alexander, Simon P.; Barros, Ana; Leinonen, Jussi; Mace, Gerald G.
Abstract: In this study, we develop statistical relationships between radar observables and drop size distribution properties in different latitude bands to inform radar rainfall retrieval techniques and understand underpinning microphysical reasons for differences reported in the literature between satellite mean zonal rainfall products at high latitudes (up to a factor 2 between products over ocean). A major assumption in satellite retrievals is the attenuation‐reflectivity relationships for convective and stratiform precipitation. They are found to systematically produce higher attenuation than our relationships with all latitudes included or within individual latitude bands (except in the tropics). The scatter around fitted curves approximating the radar reflectivity‐mass‐weighted diameter D m relationship and the dual‐frequency ratio (ratio of Ka‐ to Ku‐band reflectivities)‐ D m relationships is found to be large and of the same magnitude. This result suggests that the added value of two radar frequencies to improve the D m retrieval from space seems limited. In contrast, the relationship between D m and the attenuation/reflectivity ratio is robust and not dependent on latitude. Direct relationships between rainfall and either reflectivity or attenuation are also found to be very robust. Attenuation‐reflectivity, D m ‐reflectivity, and rainfall rate‐reflectivity relationships in the Southern Hemisphere high latitude and Northern Hemisphere polar latitude bands are fundamentally different from those at other latitude bands, producing smaller attenuation, much larger D m, and lower rainfall rates. This implies that specific relationships need to be used for these latitude bands in radar rainfall retrieval techniques using such relationships. Key Points: The relationship between radar observables and rainfall properties is different at high latitudes There seems to be limited value to the dual‐frequency GPM radar measurements for rainfall retrieval These results should help improve GPM radar rainfall retrievals